Analysis of the Effect of Intelligent Quotient (IQ),Emotional Quotient (EQ), and Spiritual Quotient (SQ) on Accountability of Private University With Performance as Intervening Variable - Mediaty; Afandi; Habbe, Abdul Hamid (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this study is to examine how intelligent quotient, emotional quotient, and spiritual quotient influence performance and accountability within private universities. The research centers on five private universities located in Makassar city, utilizing questionnaire distribution as the primary data collection method. The analysis employed for data interpretation involves quantitative methods, specifically multiple linear regression analysis and path analysis. The findings of the study reveal the following results: (1) Intelligent quotient positively influences performance in private universities; (2) Emotional quotient does not significantly affect performance in private universities; (3) Spiritual quotient positively influences performance in private universities; (4) Intelligent quotient positively affects accountability in private universities; (5) Emotional quotient positively affects accountability in private universities; (6) Accountability in private universities is positively influenced by spiritual quotient. (7) Intelligent quotient, emotional quotient, and spiritual quotient jointly contribute to a positive impact on accountability through performance in private universities.